Unravelling distinct patterns of metagenomic surveillance and respiratory microbiota between two P1 genotypes of Mycoplasma pneumoniae - Hailong You; Bin Yang; Huifang Liu; Wencai Wu; Fei Yu; Nan Lin; WenJiao Yang; Bingxue Hu; Yong Liu; Hongyan Zou; Sijia Hao; Yunping Xiao; et al. (Emerging Microbes and Infections)
To unravel distinct patterns of metagenomic surveillance and respiratory microbiota between Mycoplasma pneumoniae (M. pneumoniae) P1-1 and P1-2 and to explore the impact of the COVID-19 pandemic on epidemiological features, we conducted a multicentre retrospective study which spanned 90,886 pneumonia patients, among which 3164 cases M. pneumoniae were identified. Our findings revealed a concurrent outbreak of M. pneumoniae, with the positivity rate rising sharply to 9.62% from July 2023, compared to the 0.16% to 4.06% positivity rate observed during the 2020–2022 COVID-19 pandemic. P1-1 had a higher odds ratio of co-detecting opportunistic pathogens. However, no significant differences were observed in the co-detection odds ratio between children and other age groups in P1-2. This study is the first to demonstrate differences in relative abundance, diversity of respiratory microbiota and co-detection rate of opportunistic pathogen between M. pneumoniae P1-1 and P1-2. Through bronchoalveolar lavage (BAL) metagenomic and host transcriptomic analyses, we identified variations in co-detection rates of M. pneumoniae P1-1 genotype with opportunistic pathogens like S. pneumoniae, alterations in respiratory microbiota composition, lung inflammation, and disruption of ciliary function. Consistent with the results of host transcriptome, we found that P1-1 infections were associated with significantly higher rates of requiring respiratory support and mechanical ventilation compared to P1-2 infections (Fisher’s exact test, p-value = 0.035/0.004). Our study provides preliminary evidence of clinical severity between M. pneumoniae strains, underscoring the need for ongoing research and development of targeted therapeutic strategies.